2022
DOI: 10.1177/00220027221143963
|View full text |Cite
|
Sign up to set email alerts
|

Elite Cues and Public Attitudes Towards Military Alliances

Abstract: Do elite cues exert extensive, conditional or minimal influence on public support for military alliances in the United States? I assess the boundaries of elite leadership on public opinion towards alliances by dividing partisan respondents into wings based on isolationism and militant assertiveness. If co-partisan elite cues change public attitudes across three or four wings within their party, elites exert extensive influence. Elite cues exert conditional influence if they reach two party wings, and minimal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…The alliance effect in our experiment was much larger among NATO supporters than among NATO skeptics. Rhetoric disparaging NATO could, therefore, weaken its influence ( 32 , 37 ): if voters doubt NATO's value, they will be less motivated to take costly actions that sustain the alliance. And if potential aggressors believe that electorates are unwilling to defend allies, the threat of retaliation will become less credible, emboldening aggressors to attack ( 38–40 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The alliance effect in our experiment was much larger among NATO supporters than among NATO skeptics. Rhetoric disparaging NATO could, therefore, weaken its influence ( 32 , 37 ): if voters doubt NATO's value, they will be less motivated to take costly actions that sustain the alliance. And if potential aggressors believe that electorates are unwilling to defend allies, the threat of retaliation will become less credible, emboldening aggressors to attack ( 38–40 ).…”
Section: Discussionmentioning
confidence: 99%
“…A range of political actors have engaged in anti-NATO political rhetoric, including extreme parties in Europe (such as the National Rally in France and Die Linke in Germany), former US President Donald Trump, and Russian leaders and operatives ( 41 ). Moreover, recent studies have shown that elite rhetoric affects public opinion about the benefits and obligations of alliances ( 32 , 42 ). Our findings suggest that if criticisms of NATO are persuasive, they could erode the public's willingness to defend NATO allies and thereby encourage adversaries to attack with less fear of consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation